Study on customer satisfaction with the performance of cleaning service / Nurul Fadzlin Najwa Mohd Makki - Mohd Makki, Nurul Fadzlin Najwa (Universiti Teknologi Mara, Perak, 2018)
In this chapter, it will define on what the customer satisfaction is and how the customer satisfaction can be very important in an organization. Besides, this chapter will also explain on how the customer satisfaction can be measured and how the data is been collected. In addition, the definition of cleaning service with its purpose will be explained in this chapter. General guidelines of cleaning service which should be taken into considered to everyone is also included. There is a correlation between customer satisfactions with the performance of cleaning service which will be explained more in this chapter.